2019
DOI: 10.1002/jcb.28368
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic profiling and mRNA expression reveal candidate genes as biomarkers for colorectal cancer

Abstract: Colorectal cancer (CRC) is characterized by DNA methylation, which is associated with genomic instability and tumor initiation. As an important epigenetic regulation, DNA methylation can be used as a potential therapeutic target for CRC. In our study, we downloaded DNA methylation profiles (GSE17648 and GSE29490) and RNA sequencing microarray data (GSE25070 and GSE32323) from the Gene Expression Omnibus (GEO) database. As a result, 14 aberrantly methylated differentially expressed genes (DEGs) were screened ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…It could be inferred that the chemoradiotherapy will affect TCN1 expression through some mechanism. Zhang et al screened differentially expressed genes from the Gene Expression Omnibus database and revealed that aberrant expression of TCN1 and TGFBI was regulated by DNA methylation 28 . Lee et al performed in vitro assays and verified that downregulation of TCN1 led to an obvious reduction in the proliferation of FaDu cells.…”
Section: Discussionmentioning
confidence: 99%
“…It could be inferred that the chemoradiotherapy will affect TCN1 expression through some mechanism. Zhang et al screened differentially expressed genes from the Gene Expression Omnibus database and revealed that aberrant expression of TCN1 and TGFBI was regulated by DNA methylation 28 . Lee et al performed in vitro assays and verified that downregulation of TCN1 led to an obvious reduction in the proliferation of FaDu cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous known cancer-associated genes were included in the methylated gene set of the present study, certain of which are known to cause tumor development. For instance, the ectopic expression of transforming growth factor beta induced is associated with enhanced metastasis and extravasation of CRC (19)(20)(21). Polymeric immunoglobulin receptor promotes tumor growth in hepatocellular carcinoma (22), but inhibits pancreatic and periampullary adenocarcinoma development (23).…”
Section: Discussionmentioning
confidence: 99%
“…Coefficient values < 0 were considered statistically significant. In addition, we further performed survival analysis [ 4 ] and constructed Cox regression models [ 23 ] to screen candidate genes associated with EC progression. Based on univariate and multivariate analyses, we identified several genes with prognostic value.…”
Section: Methodsmentioning
confidence: 99%